Nursing Support During Latent Phase Labor: A Scoping Review. Issue 4 (July 2020) - Breman, Rachel Blankstein; Neerland, Carrie
Abstract: Purpose: The purpose of this scoping review was to synthesize the literature on nursing support during the latent phase of the first stage of labor. In 2014, the definition of the beginning of active labor changed from 4 centimeters (cm) to 6 cm cervical dilation. More women may have an induction of labor based on results of recent research showing no causal increase in risk of cesarean birth with elective induction of labor for low-risk nulliparous women. Therefore, in-hospital latent phase labor may be longer, increasing the need for nursing support. Design: Scoping review of the literature from 2009 to present. Methods: We conducted the review using key words in PubMed, CINAHL, and Scopus. Search terms included different combinations of "latent or early labor, " "birth, " "support, " "nursing support, " "obstetrics, " and "onset of labor." Peer-reviewed research and quality improvement articles from 2009 to present were included if they had specific implications for nursing care during the latent phase of labor. Articles were excluded if they were not specific to nursing, focused exclusively on tool development, or were from the perspective of pregnant women or providers only. Results: Ten articles were included. Results were synthesized into six categories; support of physiologic labor and birth, the nurse's own personal view of labor, birth environment, techniques and tools, decision-making, and importance of latent labor discussion during the prenatal period. Clinical Implications: Support for physiologic labor and birth is an important consideration for use of nonpharmacological methods during latent labor. The nurse's own personal view on labor support can influence the support that laboring women receive. Nurses may need additional education on labor support methods. Abstract : Recent labor management guidelines suggest longer normal limits of latent phase labor than previously acknowledged. Nursing support during latent phase labor is an important aspect of overall nursing care during labor and birth. In this scoping review, nursing care during the latent phase of the first stage of labor is explored, common themes are identified, and recommendations for practice are offered.